Facilely constructed randomly distributed surface microstructure for flexible strain sensor with high sensitivity and low detection limit. (10th May 2021) - Huang, Qi; Jiang, Yadong; Duan, Zaihua; Yuan, Zhen; Liu, Bohao; Zhao, Qiuni; Zhang, Yajie; Sun, Yupeng; Sun, Ping; Tai, Huiling
Abstract: The epidermis and dermis of human skin have randomly distributed microstructures, so we can sense external stimuli with high sensitivity and a low detection limit. Herein, a biomimetic microstructure sensor was fabricated using sandpaper as a template. The finite element simulation results show that the strain sensing property of the sensor can be improved by introducing a biomimetic microstructure, which is consistent with the experimental results. The gauge factor of the microstructure sensor (20.64) is 4.81 times that of the planar structure sensor (4.29) in the linear strain range from 0.1% to 1.0%. The microstructure sensor has a very low detection limit (0.1% strain), fast response (53.6 ms), and good cycling durability (3000 cycles). In addition, the microstructure sensor can achieve real-time monitoring of human motion and physiological signals, such as finger bending, knee bending, and breathing frequency. The proposed microstructure sensor is expected to have broad application prospects in motion monitoring and health-care fields.